Clinical pain management by a multidisciplinary palliative care team: Experience from a tertiary cancer center in China. Issue 48 (25th November 2020) - Yang, Bo; Cui, Zhi; Zhu, Xiuqin; Deng, Muhong; Pan, Yu; Li, Ruixin; Guo, Mei; Lu, Guijun; Zhang, Xuehua; Guo, Liping; Huang, Yurong; Li, Fang
Abstract : Abstract: To investigate the effect of multidisciplinary interventions on pain management in cancer inpatients. Four hundred thirty eight patients with cancer pain, who performed the multidisciplinary intervention were recruited. Before and after intervention, the Brief Pain Inventory (BPI) and the MD Anderson Symptom Inventory (MDASI) score as the primary endpoints and QOL scores as the secondary endpoint were all evaluated. To investigate the factors that led to different responses to multidisciplinary interventions, patients were classified as non-responders or responders. Finally, 92 patients (63 male and 29 female) scheduled for cancer pain management by inter-professional team were studied. After individualized multidisciplinary therapy, both pain and symptom severity was improved, as demonstrated by lowered BPI worst and average pain scores, as well as symptom severity score measured by MDASI ( P = .017, P = .003, and P = .011, respectively). The proportion of patients with mild pain increased regarding the BPI worst and average pain at baseline and after treatment ( P < .05). The QOL analyses showed multidisciplinary interventions could significantly improve the function and symptom scores ( P < .001). More patients in responder group received chemotherapy (58, 70.7%, P = .003), while fewer received mini-invasive therapy (6, 7.32%, P = .011). Multidisciplinary interventions had certain beneficial effect on cancer pain management, especially in patients with moderate or severe pain.